Profiling Socio-Demographic Characteristics of Octogenarians in Nigeria for Effective Policy Formulation: An Educational Perspective - Omoyemiju, Michael Adeniyi; Oyetunji-Alemede, Catherine Olajumoke; Aliyu, Taofeek Kolawole; Akintomide4, Akinjide Gabriel; Babalola, Oyeyemi Bukola; Ebeh, Richards Ebireonwu; Akinsooto, Tajudeen Ade; Fareo, Dorcas Oluremi; Omoteso, Bonke Adepeju; Adisa, Ademola Lateef (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The study examined the socio-demographic profile of the octogenarians in Nigeria from an educational perspective. We adopted a cross-sectional research survey design. All octogenarians in Nigeria constituted the study population. A multi-stage procedure selected a sample of 1,774 individuals. We adopted a snowball sampling approach to select participants until we reached the desired sample size. An adapted version of the World Health Organization's (WHOQOL) questionnaire programmed in the Open Data Kit (ODK) was used for data collection. We analyzed the collected data using frequency counts and simple percentages. The mean age of octogenarians was 83 years. Male-headed households were most common (66.2%) among octogenarians. Vision (8.6%) and mobility (12.1%) issues were the types of disability common to octogenarians in Nigeria. Fewer Nigerian octogenarians are still flourishing and making productive contributions to society, but a greater proportion of them need social and educational supports and physical health needs for better well-being.